The Benefits of Activating Self-Regulation Behavior in Worldwide EFL Speaking Learning Contexts - Wijaya, Kristian Florensio (SAGA: Journal of English Language Teaching and Applied Linguistics, 2025)
Transforming worldwide EFL learners into more proficient L2 speakers is a challenging mission as speaking is not merely about the meaningful communication occurrences among interlocutors but also the strong willingness shouldered by EFL learners to regulate their certain behaviors and actions to achieve the targeted learning objectives fully. The previous research results strongly suggested that EFL educators establish, nurture, and reinforce their learners’ self-regulation at the commencement of speaking-focused learning activities in order to make them more confident L2 speakers who are willing to share their thoughts with other classroom learning community members. This present small-scale library study was a little attempt initiated by the researcher to investigate the potential benefits of activating EFL learners’ self-regulation behavior in worldwide speaking learning contexts. To fulfill this main study objective, the researcher conducted a thematic analysis by reviewing 30 previous self-regulation studies conducted globally to obtain more comprehensible research results. The publication years of these 30 published self-regulation articles ranged from 2013 until 2022 to produce more reliable research results. Based on the thematic analysis, there were two major themes yielded namely: (1) Highly self-regulated EFL learners can become more organized L2 speakers, and (2) highly self-regulated EFL learners can transform into more successful L2 speakers. In conformance with these research results, second language-speaking learning instructors are strongly encouraged to cultivate self-regulation behavior within EFL learners at the beginning of learning activities to gradually make them become more high-achieving and self-reliant speakers defining the best strategies suitable for their current speaking learning situations.